Targeting Credit through Community Members. Issue 2 (9th August 2021) - Vera-Cossio, Diego
Abstract: Locally targeted programs may exploit available information transmitted through local networks to improve the selection of beneficiaries, but the effective use of this information is not granted when the selection of beneficiaries entails balancing multiple targeting criteria that are costly to verify. This paper analyzes how local committees balance issues of neediness, productivity, risk, and favoritism to allocate subsidized loans to Thai villagers. Local committees in charge of managing village funds provided credit to richer, less-productive, and elite-connected villagers threatening the program's sustainability. Informal markets partially attenuated the targeting distortions by redirecting credit from connected to unconnected households, albeit at high interest rates. Counterfactual exercises show that eliminating the connection-based distortions would reduce within-village inequality by 9.7% and modestly increase village-level output by 0.9%–1.5%.